BASIC TASKS OF TEACHING THE SCIENCE OF "EDUCATION" IN PRIMARY GRADES (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
This in the article initial in classes education science in teaching teacher in classes pedagogical technology, initial in classes interactive methods and educational games, modern information and communication from technologies use students independent thinking, creative research and makes sense thinking circles expand with together them in classes what they have learned life with to connect, their interests to increase help giving thoughts statement done